2016
DOI: 10.1080/14767058.2016.1177719
|View full text |Cite
|
Sign up to set email alerts
|

Are Asian American women at higher risk of severe perineal lacerations?

Abstract: Objective: To evaluate whether Asian race is an independent risk factor for severe perineal lacerations. Methods: We performed a nationwide population-based retrospective cohort study examining the relationship between Asian race and severe perineal lacerations (third and fourth degree). The data were collected from the 2012 Healthcare Cost and Utilization Project National Inpatient Sample (HCUP-NIS). Characteristics of Asian American women were compared with those of non-Asian women. The primary outcome of in… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
6
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 13 publications
(6 citation statements)
references
References 16 publications
0
6
0
Order By: Relevance
“…The higher the rupture grade, the longer the patient's sexual function returns to normal. 33,34 Effectiveness of Prophylactic Use Of Antibiotics In Third and Fourthdegree Perineal Rupture) The use of prophylactic antibiotics can be used in various medical indications. Especially in the perioperative period can reduce the rate of postoperative wound infection.…”
Section: Reviewmentioning
confidence: 99%
“…The higher the rupture grade, the longer the patient's sexual function returns to normal. 33,34 Effectiveness of Prophylactic Use Of Antibiotics In Third and Fourthdegree Perineal Rupture) The use of prophylactic antibiotics can be used in various medical indications. Especially in the perioperative period can reduce the rate of postoperative wound infection.…”
Section: Reviewmentioning
confidence: 99%
“…Although it has been demonstrated many times over that Asian mothers have a higher risk of severe obstetric hemorrhage, 13 intensive care unit admission, unplanned hysterectomy, uterine rupture, 14 third-degree lacerations, fourth-degree lacerations, and rectal sphincter injuries, 15 the etiology of this increased risk is poorly understood and sparsely mentioned in the literature. The invisibility of AAPI perinatal outcomes in conversations about equitable maternity care is yet another example of the erasure and minimization of our collective history.…”
Section: Silent Inequity: Asian Perinatal Morbidity and Mortality (Mjw)mentioning
confidence: 99%
“…Another Belgian retrospective study also indicated that childbirth in lateral positions could result in fewer spontaneous perineal tears and episiotomies when compared with childbirth in lithotomy positions (Inge et al, 2012). Since Asian ethnicity has been reported to be a risk factor for perineal trauma (Davies‐Tuck et al, 2015; Quist‐Nelson et al, 2017; Yeaton‐Massey et al, 2015), Chinese women may be more vulnerable to perineal trauma. However, the protective effects of lateral positions against perineum trauma among the Chinese population remain inconclusive.…”
Section: Introductionmentioning
confidence: 99%